Application of Green Chemistry by Making Eco-enzyme-Based Dishwashing Liquid Soap at Roufus Sunnah Islamic Boarding School - Alawiyah, Aika Latifah; Ruchiyat, Ruchiyat; Abdullah, Fajar Fauzi; Sari, Sinta Delia; Kamilah, Mila Wighoyatul (Fakultas Kewirausahaan Universitas Garut, 2022)
The application of green chemistry is an effort to reduce the negative impact on the environment, one of which is eco-friendly dishwashing liquid soap. It hasn’t been commonly used by the public, including Roufus Sunnah Sucinaraja Garut Islamic Boarding School students. This community service activity aims to increase students’ knowledge about eco-friendly alternative chemicals in dishwashing liquid soap products. This activity is also expected to empower students to produce dishwashing liquid soap independently and have the provisions for entrepreneurship. The method in this community service is counselling and practice in making eco-enzyme-based dishwashing liquid soap. Pre-tests and post-tests were conducted on students during the implementation of the activity. They were enthusiastic about participating in this activity. The students’ understanding increased regarding eco-friendly chemicals for dishwashing liquid soap and their skills in making these products